A mitochondria-targeting fluorescent sensor for on–off–on response to Cu2+ and ATP in cells and zebrafish. Issue 6 (22nd January 2021) - Sun, Wan; Liu, Guofeng; Tong, Mingqiong; Wang, Haozhan; Liu, Shuhan
Abstract : Cupric ion (Cu 2+ ) and adenosine triphosphate (ATP) are functionally important in mitochondria and play essential roles in many important biological processes. Abstract : Cupric ion (Cu 2+ ) and adenosine triphosphate (ATP) are functionally important in mitochondria and play essential roles in many important biological processes. In this work, a mitochondria-targeting fluorescent molecule Mito-A was used as a probe to detect Cu 2+ and ATP. The results showed remarkable fluorescence quenching of Mito-A in the presence of Cu 2+, and then the quenched fluorescence solution gradually recovered due to the ATP binding to Cu 2+ from the structure of the molecule. Mito-A has high sensitivity to Cu 2+ and ATP, with limits of detection (LOD) close to 40 nM and 0.43 μM, respectively. Cell imaging experiments showed that Mito-A has good mitochondria-targeting capabilities, and can be successfully employed for imaging Cu 2+ and ATP in living cells and zebrafish.